2011
DOI: 10.1080/10508422.2011.551470
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temporal Orientation and Affective Frame on Use of Ethical Decision-Making Strategies

Abstract: This study examined the role of temporal orientation and affective frame in the execution of ethical decision-making strategies. In reflecting on a past experience or imagining a future experience, participants thought about experiences that they considered either positive or negative. The participants recorded their thinking about that experience by responding to several questions, and their responses were content-analyzed for the use of ethical decision-making strategies. The findings indicated that a future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Process-focus while reflecting on positive past experiences increased application of experiential knowledge to future ethical decisionmaking situations Future-focused temporal orientation facilitated self-reflection and subsequent ethical decision-making (Martin et al 2011) Forecasting-making predictions about potential future outcomes through current observations Identifying critical causes in ethical dilemmas prior to forecasting facilitates accuracy in forecasting and ethical decision-making (Stenmark et al 2010) Distinguishing between critical and non-critical consequences facilitated accuracy in forecasting and ethical decision-making Information integration-combining related elements holistically via recognition of underlying conceptual relationships between issues and potential issues…”
Section: Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Process-focus while reflecting on positive past experiences increased application of experiential knowledge to future ethical decisionmaking situations Future-focused temporal orientation facilitated self-reflection and subsequent ethical decision-making (Martin et al 2011) Forecasting-making predictions about potential future outcomes through current observations Identifying critical causes in ethical dilemmas prior to forecasting facilitates accuracy in forecasting and ethical decision-making (Stenmark et al 2010) Distinguishing between critical and non-critical consequences facilitated accuracy in forecasting and ethical decision-making Information integration-combining related elements holistically via recognition of underlying conceptual relationships between issues and potential issues…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Predicting future personal experiences may also prove useful for leaders engaged in sensemaking. In their study, Martin et al (2011) investigated the role of temporal orientation (past-focused vs future-focused) and affective frame (positive vs negative) in reflecting about personal experiences while working through ethical problems. Consistent with previous research (Liberman et al 2002), this study showed that contemplating future prospective personal experiences encouraged the use of EDM strategies, leading to better decisions.…”
Section: Self-reflectionmentioning
confidence: 99%
“…Future-oriented thinking may lead patients to analyze the potential outcomes in the context of their own personal goals, thereby minimizing undesired effects (5,(16)(17)(18)(19)(20)(21)(22). However, individual patients may struggle to evaluate management choices with very different potential emotional and psychological outcomes.…”
mentioning
confidence: 99%
“…Caughron et al, 2011;Weick et al, 2005). Recently, research has focused on sensemaking in relation to EDM (e.g., Brock, et al, 2008;Martin, et al, 2011;Mumford, et al, 2008). Research shows that the sensemaking process includes a variety of metacognitive reasoning strategies.…”
Section: 22mentioning
confidence: 99%
“…Sensemaking is the retrospective activity an individual engages in to develop plausible explanations of what is happening in the current situation, to then be able to resume interrupted activity and stay in action (Weick et al, 2005). In order to make sense of the situation they encounter, individuals engage in certain sensemaking strategies and tactics that emerge from both an emotional as well as a rational foundation (e.g., Martin et al, 2011). …”
mentioning
confidence: 99%